2014
DOI: 10.1121/1.4863646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disfluent speech by means of automatic acoustic measurements

Abstract: An experiment was carried out to determine whether the level of the speech fluency disorder can be estimated by means of automatic acoustic measurements. These measures analyze, for example, the amount of silence in a recording or the number of abrupt spectral changes in a speech signal. All the measures were designed to take into account symptoms of stuttering. In the experiment, 118 audio recordings of read speech by Czech native speakers were employed. The results indicate that the human-made rating of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…A primary feature of stuttering is involuntary pauses known as blocks, and such pauses have been found to be important in assessing fluency of speech [11, 34]. Like the differences in the pause lengths in the Gnptab mut/mut mice and Gnptab wt/wt mouse vocalizations, the speech of PWS had significantly longer pauses between vocalizations compared to that of control subjects (PWS 0.385 ± 0.021 sec; CT, 0.170 ± 0.005 sec; t -test, p < 10 -12 , Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary feature of stuttering is involuntary pauses known as blocks, and such pauses have been found to be important in assessing fluency of speech [11, 34]. Like the differences in the pause lengths in the Gnptab mut/mut mice and Gnptab wt/wt mouse vocalizations, the speech of PWS had significantly longer pauses between vocalizations compared to that of control subjects (PWS 0.385 ± 0.021 sec; CT, 0.170 ± 0.005 sec; t -test, p < 10 -12 , Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
“…Stuttered speech has been extensively analyzed using a variety of measures including words per minute, voice onset time, formant frequencies of consecutive glottal periods, and other language-based acoustic techniques [31, 33, 34, 40]. Previous studies have demonstrated that stuttering is strongly correlated with fewer vocalizations per unit time and an increase in pause length [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…This requires considerable time and labor, making such tools impractical for busy clinicians. Many authors have put substantial research effort in to automate the analysis for clinical assessment of disordered speech (Berisha et al, 2013;Bocklet et al, 2012;He et al, 2013;Lustyk et al, 2014;Maier et al, 2009;Middag et al, 2009;Zhou et al, 2012). Landmark (LM) analysis is a novel approach that characterizes speech with acoustic markers that are developed based on the LM theory of speech perception.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed description of the measures is given in [20] where experiments on read stuttering recording of Czech speakers are carried out.…”
Section: Algorithmsmentioning
confidence: 99%